Impact of prior rituximab on outcomes of autologous stem‐cell transplantation in patients with relapsed or refractory aggressive B‐cell lymphoma: a multicentre retrospective Spanish group of lymphoma/autologous bone marrow transplant study. (26th November 2013) - Redondo, Alba M.; Pomares, Helena; Vidal, María J.; Pascual, María J.; Quereda, Belén; Sancho, Juan M.; Polo, Marta; López, Javier; Conde, Eulogio; Jarque, Isidro; Alonso, Natalia; Ramírez, María J.; et al.
Summary The use of highly effective rituximab‐containing therapy for treating diffuse large B‐cell lymphoma (DLBCL) makes it more difficult to salvage relapsed or refractory patients. Autologous stem‐cell transplantation (ASCT) is the reference treatment for these patients, but the impact of previous exposure to rituximab on the subsequent results of ASCT remains unknown. We analysed 248 patients with relapsed or refractory DLBCL or grade 3B follicular lymphoma pre‐treated with rituximab as part of first‐line therapy (R+ group) who received ASCT, in comparison with a control group of 127 patients without previous exposure to rituximab (R− group). The complete remission (CR) rates were similar in both groups. Multivariate analysis identified age‐adjusted International Prognostic Index at diagnosis, extranodal involvement and disease status at transplant, and the number of previous chemotherapy lines as independent factors with a negative influence on CR rate. Compared with R− patients, those in the R+ group had a significantly better progression‐free survival (63% vs. 48% at 5 years) and overall survival (72% vs. 61% at 5 years). This observation was independent of other prognostic factors that affected these outcomes. In conclusion, ASCT is no less effective in patients with relapsed or refractory aggressive B‐cell lymphoma pre‐treated with first‐line rituximab‐containing therapy than in rituximab‐naive patients.